Effect of white kabesak (Acacia leucophloea Roxb) leaves level in the diet on feed intake and body weight gain of Kacang goat - Lawa, E. D. W.; Marjuki, M.; Hartutik, H.; Chuzaemi, S. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
This study was conducted to analysis the effect of levels of white kabesak (Acacia leucophloea Roxb.) Willd. leaves in the diet on feed intake, digestibility and body weight gain of Kacang goats. The completely randomized block design using 5 treatments and 5 replications was used in this experiment. The treatments were 5 concentrate feeds containing different levels of white kabesak leaves i.e. 0, 10, 20, 30 and 40% in the dry matter (DM) basis (representing T0, T1, T2, T3 and T4 treatments, respectively). The feeds were set up to contain 11.5-12.5% of crude protein (CP). Concentrate feed and native grass was fed at ratio of 60 : 40 was fed to 5 local male goats (age 1-1.5 years old and initial weight of 16.7±5.0 kg). The results showed that DM, organic matter (OM), and CP intake of T0 was not significantly different from those of T1 goats, but it was significantly higher (P<0.05) than those of T2, T3 and T4. The DM, OM, CP, and crude fiber (CF) digestibility as well as body weight gain in T2 goats were significantly higher (P<0.05) and had feed conversion ratio that was significantly better (P<0.05) compared to those of the other feed treatments. In conclusion, the most optimum level of white kabesak (Acacia leucophloea Roxb.) Willd. leaves used in concentrate feed for goat was 20 %.